Cuidados Paliativos e Cuidados ao Fim da Vida na Velhice* - Ligia Py; Claudia Burlá; Carmen Saiz Limoeiro; Fátima Cristina Melo Geovanini; Ciro Augusto Floriani; Daniel Azevedo; Dulcinea Monteiro; José Francisco Oliveira; Rachel Aisengart Menezes; Samuel Rodrigues de Souza; Silvia Pereira; Virgílio Garcia Moreira (Brazilian Society of Geriatrics and Gerontology, 2024)
Nenhum.